2002
DOI: 10.1046/j.1365-2249.2002.01898.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human natural killer cell activity by cereulide, an emetic toxin fromBacillus cereus

Abstract: SUMMARY The lipophilic toxin, cereulide, emitted by emetic food poisoning causing strains of Bacillus cereus, is a powerful mitochondria toxin. It is highly lipophilic and rapidly absorbed from the gut into the bloodstream. We tested how this toxin influences natural killer (NK) cells, which are important effectors in defence against infections and malignancy. Cereulide inhibited cytotoxicity and cytokine production of natural killer cells, caused swelling of natural killer cell mitochondria, and eventually in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
48
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(49 citation statements)
references
References 32 publications
0
48
0
1
Order By: Relevance
“…Cereulide is a small, heat-and acid-stable cyclic dodecadepsipeptide (Agata et al, 1994) and is synthesized by a non-ribosomal peptide synthetase, encoded by the ces genes (Ehling-Schulz et al, 2005). It has been shown to cause cellular damage in animal models (Shinagawa et al, 1995) and it has been reported that cereulide inhibits human natural killer cells and might therefore have an immunomodulating effect (Paananen et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Cereulide is a small, heat-and acid-stable cyclic dodecadepsipeptide (Agata et al, 1994) and is synthesized by a non-ribosomal peptide synthetase, encoded by the ces genes (Ehling-Schulz et al, 2005). It has been shown to cause cellular damage in animal models (Shinagawa et al, 1995) and it has been reported that cereulide inhibits human natural killer cells and might therefore have an immunomodulating effect (Paananen et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The emetic toxin is produced by vegetative B. cereus cells in food before ingestion and remains active upon stomach transit. It is toxic to mitochondria by acting as a potassium ionophore (38) and has been reported to inhibit human natural killer cells (43). The diarrheal syndrome is caused by enterotoxins secreted by vegetative cells in the small intestine, where they can act by disrupting the integrity of the membrane of epithelial cells (56).…”
mentioning
confidence: 99%
“…Besides these less acute symptoms, a number of studies have indicated a high toxicity potential concerning immunomodulatory and neuro-and hepatotoxic modes of action (4,39,44). Due to their lower toxic capacity, children and immunosuppressed individuals are especially vulnerable, and cases of fatal liver failure or encephalopathy have been reported (10,31,49,59).…”
mentioning
confidence: 99%